Hiding a Hurricane Under a Beach Umbrella: Fitzgerald's Tender Is the Night's Ecological Latencies - DeGuzmán, María (The Trumpeter, 2024)
At first glance, Fitzgerald’s Tender Is the Night seems like a far cry from what Matthew M. Lambert has termed “Green Depression” literature. Philip Rahv’s critique that Tender attempted to hide from a hurricane under a beach umbrella tagged it with the lingering perception that it was incongruously out of touch with its era’s “climate.” Revisiting Tender through the lens of Antonioni’s 1960 film L’avventura that showcases a copy of Fitzgerald’s novel, this article looks back on the novel itself to reveal the powerful undertow of its “ecological latencies,” which were there all along in submerged and “dormant” form. The creation of this lens through which to view Tender Is the Night does not mean that this article aims to offer a comparative reading of Antonioni’s film and Fitzgerald’s novel. Side-by-side formal comparison is not the goal of this article. Rather, the article underscores a carefully staged yet critically overlooked reference in Antonioni’s 1960s film itself—to Fitzgerald’s Tender Is the Night—in order to offer a completely new reading, an ecologically engaged one, of Fitzgerald’s 1934 novel.